2008
DOI: 10.1094/pdis-92-1-0158
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Epidemiology of Monosporascus Root Rot and Vine Decline in Muskmelon, Watermelon, and Grafted Watermelon Crops

Abstract: Disease progression and soil population dynamics of Monosporascus cannonballus ascospores were studied and compared through the entire growing season in muskmelon, watermelon, and watermelon grafted onto Cucurbita rootstock crops. In muskmelon and watermelon, there was a decrease of ascospore counts in soil from transplanting until first symptoms of vine decline were observed. This decrease probably was related to ascospore germination and subsequent root infection. Later, there was a remarkable increase of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…As previously mentioned, no ascospores germinated in the rhizosphere of C. maxima and cultivars of this cucurbit are currently employed as M. cannonballus-resistant rootstocks for grafting of susceptible melons scions (Edelstein et al, 1999;Cohen et al, 2000Cohen et al, , 2005Beltrán et al, 2008). Lack of ascospore germination, as documented in this study, provides direct evidence in support of the conclusion of Beltrán et al (2008) that resistance of squash rootstock resides in the 'lack of recognition between the host and the pathogen'. Further, our experiments involving co-cultivation of 'Brava' and 'Caravelle' in the same soil assay tube demonstrated that exudates from 'Brava' did not inhibit ascospore germination and that ascospores stimulated to germinate by 'Caravelle' roots did not attach to 'Brava' roots.…”
Section: Ascosporessupporting
confidence: 85%
“…As previously mentioned, no ascospores germinated in the rhizosphere of C. maxima and cultivars of this cucurbit are currently employed as M. cannonballus-resistant rootstocks for grafting of susceptible melons scions (Edelstein et al, 1999;Cohen et al, 2000Cohen et al, , 2005Beltrán et al, 2008). Lack of ascospore germination, as documented in this study, provides direct evidence in support of the conclusion of Beltrán et al (2008) that resistance of squash rootstock resides in the 'lack of recognition between the host and the pathogen'. Further, our experiments involving co-cultivation of 'Brava' and 'Caravelle' in the same soil assay tube demonstrated that exudates from 'Brava' did not inhibit ascospore germination and that ascospores stimulated to germinate by 'Caravelle' roots did not attach to 'Brava' roots.…”
Section: Ascosporessupporting
confidence: 85%
“…Owing to its tolerance, autumn squash is routinely used as a rootstock for both muskmelon and watermelon in order to control soil-borne diseases, such as Fusarium wilt (Miguel et al 2004), Acremonium collapse (in watermelon; Armengol et al 1998) and Monosporascus wilt (in muskmelon; Cohen et al 2005;in watermelon;Beltrán et al 2008). Furthermore, research indicates that the symptoms caused by both fungi are more severe in melons and watermelons than in squash (Aegerter et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Tests conducted in Spain with watermelon grafted onto Cucurbita rootstock showed no signs of disease. M. cannonballus was isolated from the roots but at lower frequencies than in Texas (Mertely et al 1993a) and perithecia were not observed (Beltr an et al 2008). In addition, the population of ascospores in the soil remained stable during the season.…”
Section: Role Of Root Architecture and Morphology In Resistancementioning
confidence: 95%
“…Interspecific grafting of melons with other cucurbits has the potential to reduce damage caused by M. cannonballus and other soilborne pathogens (Cohen et al 2007;Davis et al 2008). Most cucurbits other than melon and watermelon reportedly do not experience much disease in the field due to M. cannonballus, in spite of the fact that they are susceptible (Uematsu et al 1992;Mertely et al 1993a;Beltr an et al 2008). This is generally believed to be due to the extensive root systems produced by plants in the genera Cucurbita and Lagenaria, which can provide sufficient support to the vines and fruits in spite of some infection.…”
Section: Role Of Root Architecture and Morphology In Resistancementioning
confidence: 99%